2004
DOI: 10.1089/104454904322759920
|View full text |Cite
|
Sign up to set email alerts
|

Human Lectin-Like Oxidized Low-Density Lipoprotein Receptor-1 Functions as a Dimer in Living Cells

Abstract: Lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) is a unique scavenger receptor that plays important roles in atherogenesis and has been thought to function as a monomer. Using coimmunoprecipitation studies, we demonstrate that human LOX-1 (hLOX-1) forms constitutive homo-interactions in vivo. Western blot analysis of cell lysates under nonreducing or reducing conditions revealed one clear immunoreactive species corresponding to the size of a putative receptor dimer or a monomer, respectively, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 24 publications
0
43
0
2
Order By: Relevance
“…Our analysis of MICL, in both transduced cell lines [14] and primary cells, suggests that this molecule is highly N-glycosylated compared to its most closely related paralogs, lectin-like receptor for oxidized LDL [22], Dectin-1 [9,23], and CLEC-2 [13]. Intriguingly, the level of MICL N-glycosylation varied significantly in different leukocyte populations, which may have functional consequences for ligand binding, as shown for other receptors [24,25].…”
Section: Discussionmentioning
confidence: 64%
“…Our analysis of MICL, in both transduced cell lines [14] and primary cells, suggests that this molecule is highly N-glycosylated compared to its most closely related paralogs, lectin-like receptor for oxidized LDL [22], Dectin-1 [9,23], and CLEC-2 [13]. Intriguingly, the level of MICL N-glycosylation varied significantly in different leukocyte populations, which may have functional consequences for ligand binding, as shown for other receptors [24,25].…”
Section: Discussionmentioning
confidence: 64%
“…Mutation of Cys140 does not affect the ox-LDLbinding activity [9,10] and does not destabilize the dimeric form of the ligand-binding domain [10]. The particular dimeric association of CTLD in human LOX-1 generates a tunnel which completely crosses the dimer with a diameter of 7.0-8.0 Å, except for a first constriction caused by the side chains of Ile149 of the two subunits and a second constriction caused by Tyr197 of subunit A, that restrict the opening to 4.0 Å [7].…”
Section: Introductionmentioning
confidence: 95%
“…LOX-1 is heavily modified by N -linked carbohydrate, and experiments with tunicamycin-treated cells have suggested that this N -linked glycosylation may contribute to OxLDL binding (87). Interestingly, Xie et al (88) recently reported that human LOX-1 functions as a disulfide-linked homodimer at the cell surface. In addition to acting as a membrane receptor for OxLDL, soluble forms of LOX-1 have been identified that are secreted by tumor necrosis factor-␣ -stimulated endothelial cells (89).…”
Section: Lox-1mentioning
confidence: 99%